The new bone formation in human maxillary sinuses using two bone substitutes with different resorption types associated or not with autogenous bone graft: a comparative histomorphometric, immunohistochemical and randomized clinical study - Rodrigo dos Santos PEREIRA; João Paulo BONARDI; Felippe Ricardo Frossard OUVERNEY; Annelise Backer CAMPOS; Geraldo Luiz GRIZA; Roberta OKAMOTO; Eduardo HOCHULI-VIEIRA (University of São Paulo, 2020)
Abstract Objective The aim of this study is to evaluate the new bone and connective tissue formation and the biomaterial remaining after maxillary sinus bone augmentation using 5 different bone substitutes. The osteocalcin immunolabeling was performed to demonstrate their calcification and the possibility of receiving dental implants. Methodology 40 patients underwent maxillary sinus bone augmentation and were divided in 5 groups: Group 1 with 8 maxillary sinuses were grafted with autogenous bone graft (AB); Group 2 with 8 maxillary sinuses grafted with bioactive glass (BG); Group 3 with 8 maxillary sinuses grafted with bioactive glass added to autogenous bone graft (BG + AB) 1:1; Group 4 with 8 maxillary sinuses grafted with Bio-Oss (BO) and Group 5 with 8 maxillary sinuses grafted with Bio-Oss added to autogenous bone graft (BO + AB) 1:1. Results In group AB, 37.8% of bone was formed in the pristine bone region, 38.1% in the intermediate and 44.5% in the apical region. In group BG, 43.6% was formed in the pristine bone, 37% in the intermediate and 49.3% in the apical region. In group BG + AB 1:1, 39.0% was formed in the pristine bone region, 34.8% in the intermediate and 36.8% in apical region. In group BO, 33.4% was formed in the pristine bone, 32.5% in the intermediate and 34.3% in the apical region. In group BO + AB 1:1, 32.8% was formed in the pristine bone, 36.1% in intermediate and 27.8% in the apical regions. The immunolabeling for osteocalcin showed an intensive staining for all groups, which could demonstrate the calcification of the bone formed. Conclusion This study showed that the groups evaluated formed a suitable lamellar bone in the maxillary sinus reconstruction after six months of bone healing, thus being indicated to receive dental implants.